Pablo Picasso's first incursions into The New Technologies of The Early Twentieth Century: The Barcelona Napoleon Cinimatograph as paradigm (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
Throughout this article we will approach Pablo Picasso's first forays into new technologies at the beginning of the 20th century. As a representative example of these new technological methods of the time, we will analyze the relationship that was established between Pablo Picasso and cinema, through the specific study of the links that were established between the artist and Cinematographer Napoleon of Barcelona, during his youth. From here, we will assess what degree of influence the cinema had on the early work of Pablo Picasso by comparing various data and testimonies collected from authors such as Roland Penrose, Pierre Cabanne, Pierre Daix, Palau i Fabre or John Richardson, among others. , which point out relevant connections between certain films shown in Barcelona during the first years of the 20th century at the Cinematografía Napoleón and some works by Picasso made in the same period.
Keywords: Pablo Picasso; Napoleon Cinematographer; Cinema; New Technologies; Cubism